Conflict: Readings in Management and Resolution
XXIV, 354 p.
Keywords: Conflict resolution is now recognized as a major area of research. Yet because of its pervasive nature as a subject, drawing on so many different disciplines, there has long been a need for a reader, bringing together many of the most important and representative essays written to date. This book aims to fill the gap. Equally important, a comprehensive bibliography further anchors the subject - providing academics, diplomats, students and others interested in conflict studies with an excellent basis for future research.